Bombesin-like peptides: Candidates as diagnostic and therapeutic tools - YEGEN, BERRAK (BENTHAM SCIENCE PUBL LTD, 2003)
Bombesin (BBS) is proved to have a wide variety of the pharmacologic effects, including effects on the release of gastrointestinal hormones and control of gastrointestinal motility. More recently, the role of BBS in tumor growth, cellular proliferation and inflammation has attracted attention. There is evidence that increased BBS receptor expression may be considered as a specific marker for small-cell lung cancer, colorectal adenocarcinoma. gastric and pancreatic cancer, prostate, ovarian and breast cancer, neuroblastoma, renal ell carcinoma, malignant melanoma and thyroid carcinoma. BBS expression was found to be correlated with the histological grade of the tumor. Similarly, BBS treatment significantly improves the healing of chronic gastric ulcers and ameliorates the severity of burn- or colitis-induced gut injury. Although there is much complexity still to be elucidated to understand fully the physiologic and pathologic roles of BBS-like peptides several clinical or experimental trials have addressed that circulating or tissue levels of BBS-like peptides or their receptor expression may be used as diagnostic or prognostic markers of neoplastic disease, and incorporation of BBS receptor antagonists in the treatment of human cancer could provide substantial benefit to the cancer patients. Moreover, trophic, anti-ulcerogenic and anti-inflammatory actions of exogenous BBS make this peptide a potential supplement in minimizing or reversing tissue damage against several injurious challenges. In conclusion, based on the evidence summarized herein, related to the mitogenic and anti-inflammatory effects of BBS-like peptides, further investigations are needed to derive the benefit of BBS-like peptides in pharmacologic strategies.
Keywords: anti-ulcerogenic effect; mitogenic; trophic; tumor growth; bombesin receptor expression; GASTRIN-RELEASING-PEPTIDE; SWISS 3T3 CELLS; CHOLECYSTOKININ-A-RECEPTOR; NERVOUS-SYSTEM ACTION; GASTROINTESTINAL-TRACT; ACID-SECRETION; LUNG-CARCINOMA; BINDING-SITES; NEUROMEDIN-B; RAT-BRAIN